Analysis of Security Mechanisms in Nigeria E-Banking Platform - Ayangbekun Oluwafemi J.; Bankole O. Felix; Saka Badirat A. (International Journal of Electrical and Computer Engineering (IJECE), 2014)
Electronic banking system has become an important practice among all banks in Nigeria. The introduction of this electronic banking has improved banking efficiency in rendering sales and services to customer, which is the 24-hour access to cash and retrieval of banking data i.e. statements, transaction details etc. It was in line with this that the studies aim at the Security Mechanisms of E-banking System. Through the cluster sampling technique, data was collected by means of questionnaires from 25 Banks officers and the result shows Electronic Banking is barely secure for the financial institutions. And through the hypothesis carried out in this research, it shows us that all banking transaction can be done anywhere is the world as long as your access device is connected to the internet service through any service provider. This Mechanism was initialized and found to be very effective for securing the banking transactions. It’s being recommended for banks and other financial institutions for maximum security.  With all these in the banking Industry, the bank has an effective electronic banking system which has improve its customer’s relationship and satisfaction. To this end, it is recommended that the bank information and Communication technology training programme should be encourage among all the banks staff, necessary legal codes banking should be established in order to enhance growth of the industry.DOI:http://dx.doi.org/10.11591/ijece.v4i6.6857